PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA, CITRA,DAN POSITIVE WORD OF MOUTH POLITEKNIK NEGERI BALI - I Komang Mahayana Putra; Nyoman Kerti Yasa (Jurnal Bisnis dan Kewirausahaan, 2015)
Service quality has significant influence on customer satisfaction, image and positive word of mouth. This has been demonstrated by the majority of research . However, only few research that focus on the service quality of the higher education institution which aiming at identifying student satisfaction. The purpose of this research is to discover the influence of service quality on student satisfaction, image and positive word of mouth of Bali State Polytechnic. The research is conducted by utilizing quantitative method. Data is gathered by administering the questionaires to 170 students of Bali State Polytechnic which are determined by purposive proportional sampling method. Data is analyzed by applying the Structural Equation Modeling (SEM) computerized by AMOS Version 21 The result of this research reveals that service quality has positive and significant influence on student satisfaction, image of Bali State Polytechnic and positive word of mouth. The Bali State Polytechnic students satisfaction has positive and significant influence on Bali State Polytechnic image and positive word of mouth of Bali State Polytechnic. The image of Bali State Polytechnic has positive and significant influence on positive word of mouth Bali State Polytechnic. This research has the implication to the service provided by Bali State Polytechnic. The research finding contributes to maintain and improve Bali State Polytechnic image. Recommendations for Bali State Polytechnic are the necessity in improving the library collections, improving the cleanliness of the toilet, improving the staff competency in delivering the service, and improving the willingness of staff and lectures to provide excellence service to the student.